Trees and Shrubs of Kentucky - Wharton, Mary E., 1912-1991 (Book collections on Project MUSE., 1973)
This authoritative volume provides a comprehensive guide to the 282 species of woody plants found in Kentucky, Illinois, Indiana, Ohio, Pennsylvania, West Virginia, Virginia, Tennessee, and Eastern Missouri. Illustrated with more than 1,150 photographs, this book shows not only leaves and bark, but also buds, flowers, and fruits to enable you to recognize trees at any season. Complete with an identification guide that really works, this beautiful book will be valuable to both specialist and amateur.